Successful Wildlife Conservation Requires Good Governance - Pomeranz, Emily F.; Hare, Darragh; Decker, Daniel J.; Forstchen, Ann B.; Jacobson, Cynthia A.; Smith, Christian A.; Schiavone, Michael V. (Frontiers in Conservation Science, 2021)
Public wildlife management in the United States is transforming as agencies seek relevancy to broader constituencies. State agencies in the United States, while tasked with conserving wildlife for all beneficiaries of the wildlife trust, have tended to manage for a limited range of benefits in part due to a narrow funding model heavily dependent on hunting, fishing, and trapping license buyers. To best meet the needs, interests, and concerns of a broader suite of beneficiaries, agencies will need to reconsider how priorities for management are set. This presents an opportunity for conservation program design and evaluation to be elevated in importance. We argue that success in wildlife conservation in the U.S. requires assessment of both decision-making processes and management results in relation to four questions: conservation of what, under what authority, for what purposes, and for whom?